Automated Court Decision Platform in Ecuador: Advancing Judicial Processes through Information and Communication Technologies - Reyes-Lopez, Christopher Ruben; Centeno-Rodríguez, Rafael Luis (LACCEI, 2024)
The integration of information and communication technologies (ICTs) and artificial intelligence (AI) to justice system institutions, around the world, has been lately used to improve their management and performance. Such incorporation lets courts automate routine administrative tasks, allowing legal professionals to focus on more complex and strategic aspects of their work. All this can be achieved through the development and use of technological tools that simplify and speed up tasks, resulting in the amelioration of the management and processing of cases, the enrichment of the quality of information, and the facilitation of judicial decision-making. In this context, this paper aims to identify the automated court decision platforms (ACDP), focusing on the technology behind it. ACDP is a cutting-edge system designed to revolutionize the process of generating court decisions; however, some of those who know and work in the Ecuadorian Judiciary are somewhat opposed to the digitalization of verdicts. Awareness rises among the interviewees who participated in a small focus group prepared to discuss these formats. Participants remark on how mediation by the Judge bear personalized solutions based on verbal and nonverbal interactions with the intervening parties, especially considering that the concepts and topics covered are as ethereal as justice and equity.